Probiotics in the prevention and treatment of calcium oxalate kidney stones: mechanisms and therapeutic potential - Yang, Jinshan; Li, Dengbao; Li, Tao; Jia, Benzhong (Frontiers in Microbiology, 2025)
BackgroundKidney stones, particularly calcium oxalate stones, remain a significant health issue despite advances in treatment techniques. Residual stones that persist after treatment can lead to recurrent stone formation and further complications. The role of gut microbiota, specifically probiotics, in modulating oxalate metabolism has gained increasing attention as a potential therapeutic strategy to reduce residual stones and prevent recurrence.SummaryThis paper reviews the potential of probiotics, including recombinant strains, in the treatment of calcium oxalate kidney stones. Probiotics are thought to promote the degradation of oxalate in the gut, thereby reducing its absorption and preventing stone formation. Recent studies have highlighted the beneficial effects of probiotic interventions on gut microbiota composition, oxalate degradation pathways, and calcium oxalate stone formation. Moreover, recombinant probiotics, engineered to enhance oxalate-degrading capabilities, hold promise for improving treatment outcomes.Key messagesThis review summarizes recent advancements in the use of probiotics for the prevention and treatment of calcium oxalate kidney stones, with a focus on their role in oxalate degradation and the potential of recombinant probiotics to improve treatment outcomes.